FRAKSIONASI DAN PENENTUAN PROFIL PROTEIN BUNGKIL KELAPA DENGAN SDS-PAGE [Fractionation and Profiling of Copra Meal’s Protein by Using SDS-PAGE] - Agus Danang Wibowo; Maggy T. Suhartono; Patuan L. P. Siagian (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2012)
The aim of this research was to extract proteins from the copra meal, base on their solubility and analysis of the protein profiles by Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis (SDS PAGE) This research was conducted in two stages, protein fractionation and molecular weight estimation using SDS PAGE. The fractionation was conducted by non-enzymatic treatment and enzymatic (mannanase) treatment. Kjeldahl analysis showed that the protein content of copra meal was 18.52% of dry basis. Protein fractionation could separate the copra meal’s proteins based on their solubility. Albumin was solubilized by water, globulin by NaCl 5%, glutelin by NaOH 0.02M, and prolamin by ethanol 70%. Fractionation using non-enzymatic treatment resulted in 64% of albumin, 39.25% of globulin, 15.27% of glutelin, and 38.84% of prolamin fractions. On the other hand, fractionation using enzymatic treatment resulted different protein profile, giving 28.17%, 39.44%, 10.91%, and 21.48% of the respective proteins. Characterization using SDS PAGE showed that the protein profile from the non-enzymatic was different from that of the enzymatic treatment. In conclusion, we found that the proteins extracted from the copra meal with and without mannanase showed variation in the range of molecular weights: 45.1-66,0 kDa and 66.1-97.4 kDa, respectively.